Numerical Modeling of Bioinspired Tri-Layer Scaffolds for Heart Valve Constructs - Liu, Yueen (Université d'Ottawa / University of Ottawa, 2025)
For many patients suffering from heart valve diseases, heart valve replacement surgery is the primary treatment option. Currently, there are two types of artificial valves clinically available for the replacement surgery, the mechanical valve and the bioprosthetic valve. The former is typically made from durable materials and can last for a long time. However, lifelong medical treatment with blood thinner is required to reduce the clot risk. The latter is generally made from animal valves and could avoid the long-term use of medication. However, it suffers from biocompatibility issues and relatively short service life due to calcification. With the recent advancement in tissue engineering, tissue-engineered heart valves provide a promising potential to overcome the limitations of the existing artificial heart valves. Among various fabrication methods, the electrospinning technology offers an effective approach to fabricate scaffold materials needed in the artificial heart valve. In order to ensure that the fabricated scaffold material mimics the mechanical properties of native valve tissues, solely relying on experimental trial-and-error is labor-intensive, time-consuming, and financially expensive. On the other hand, numerical methods, especially finite element simulations, provide an efficient approach to investigate the mechanical properties of fabricated scaffold materials. In this thesis, a computational framework based on the finite element method is developed to model the mechanical responses of the bioinspired tri-layer scaffold used for heart valve constructs. This scaffold material is composed of a top layer and a bottom layer containing mutually orthogonal fiber alignments as well as a middle layer possessing a honeycomb pattern. A hyperelastic material constitutive model is developed as the material constitutive model, and a three-field mixed finite element approach is adopted to enforce the material incompressibility. The details of the developed numerical technique are presented, including the material constitutive formulation and the finite element approach in the framework of the nonlinear solid mechanics. The obtained numerical results are compared with the experimental observations, and the detailed stress distributions among various scaffold layers are revealed. The force-displacement relationship confirms that the fabricated tri-layer scaffold exhibits similar mechanical properties as native heart valve tissues.
Keywords: Biomimetic; Heart valve; Layered structure; Finite element modeling